Fractal characteristics of gas migration channels at different mining heights. (1st July 2020) - Zhao, Pengxiang; Zhuo, Risheng; Li, Shugang; Lin, Haifei; Shu, Chi-Min; Laiwang, Bin; Jia, Yongyong; Suo, Liang
Highlights: A model was proposed for predicting fractal dimensions at different mining heights. The primary controlling factors for gas migration channel boundaries were identified. The channel was divided into three areas based on fractal dimensions in a vertical gradient. The proposed new model could be better estimated the position of high-level boreholes. Abstract: Fracture randomness and irregularities have a decisive effect on the gas reservoir and migration in overlying strata at different coal mining heights. To determine the boundary of a gas migration channel, its effect on gas storage, and migration in the overlying strata at different coal mining heights, this study integrated the two-dimensional (2D) physical similarity simulation of the calculated fractal dimensions to examine the results obtained using analytical techniques. With the increase of the mining height, the range of gas migration channels increased significantly. Moreover, we identified the primary parameters of the gas migration channel boundary in the mutant regions of bed separation and the broken fracture density. Apart from the increasing working distance, the fractal dimension increased when the fractal dimension of a working face side was larger than an open-off cut side. The fractal dimensions of a mine with a height of 6.0 m were 1.07 and 1.23 times of those for heights of 4.0 and 2.0 m, respectively. According to the variation principle of fractal characteristics and Reynolds number, the gas migration channel was divided into three regions, namely a gas active, gas circulation, and gas enrichment areas. On the basis of the fractal theory, an effective model was proposed to calculate the evolution characteristics of gas migration channels at different mining heights. Compared with the previous gas migration channel model, the proposed model could be appropriately estimated the position of high-level boreholes; the improved estimations can improve gas drainage efficiency and ensure safe and efficient mining.